Identifying The Problems Experienced By Families Of Children With Burn Injuries After Discharge And The Causes Of These Problems - Nazife Gamze Özer; Fatma Vural (Galenos Publishing House, 2020)
INTRODUCTION: Burns alter normal life processes suddenly. It is hard both to accept burns due to accompanying physical and psychological changes and to learn how to live with the generally altered appearance caused by them. The study was conducted to identify the problems experienced by families of children with burn injuries after discharge and the causes of these problems. METHODS: The descriptive study data were collected with the help of an introductory form, an information form for the problems experienced by parents and the State Anxiety Inventory. Statistical Package for the Social Sciences 16.0 program was used in data analysis. Study data were expressed as numbers, percentages, means using Student's t test. RESULTS: The sample included 162 families of children with burns. Of these children, 54.3% were males, while 70.4% of them had scalding and 46.3% had superficial burns. Families had experienced problems with their children concerning bathings (81.5%), social communication (77.8%), getting dressed (63.0%), using medications (61.7%), doing exercises (54.3%), feeding ( 40.7%) and dressing wounds (34.6%). Mean state anxiety score was found to be 47.03+-7.48. DISCUSSION AND CONCLUSION: This study found that parents experienced various problems after discharge: Problems with using medication, dressing wounds, bathing, getting dressed, exercise, nutrition and social communication were experienced. It was determined that problems experienced affected the anxiety levels of the families. It is suggested for nurses to provide regular home visits or provide consultancy via telephone in order to identify problems.Identification of the problems expeirenced will also contribute to the preparation of the content discharge training programs.